Evaluation of Native Rhizobia Strains on the Growth and Yield Attributes of Rainfed Chickpea - Al-Khateeb, Rawan Haya Adnan; Gharraa, Mahmoud Abu; Al-Shater, Mohammad Said (Annals of Arid Zone, 2020)
This research aims to explore the effect of inoculation with nitrogen-fixing bacteria and with or without chemical nitrogen fertilizer on the growth and productivity of chickpea under field conditions. The experiment was carried out in split-plot design with three replicates at Hout Research Station of Agricultural Scientific Research Center in As-Suwayda governorate. Nitrogen fertilizer treatments (N 0%, N 100% of recommended dose) were according to the ministry of agriculture recommendation; the bacterial treatments were ten (eight treatments were inoculation with different chickpea bacterial isolates and a ninth one was inoculation with mixture of eight isolates and the tenth was uninoculated control treatment). The results showed that the isolates R1, R4 and R8 exceeded all others in terms of productivity (t ha-1), weight of dry matter, weight of dry nodules per plant (g plant-1), plant height (cm) and seeds number per plant. As for the interaction between bacterial inoculation and chemical nitrogen fertilization, the treatments R1 N 100% and R4 N 100% exceeded all others in terms of all the studied parameters of growth and productivity. Rhizobia inoculation and chemical nitrogen fertilization for the treatments R1 N 100% increased the weight of dry nodules per plant by 228.66% compared to non-inoculated plants. Results indicated that application of suitable amounts of N fertilizer can be beneficial to improve nodulation, growth, and final yield of inoculated chickpea plants. Based on results, it can be concluded that the two strains R1 and R4 can be promising to increase the growth and productivity of chickpea plants. Key words: Rainfed chickpea, nitrogen fixing bacteria, nitrogen fertilization, bio-fertilizer, Rhizobia, productivity.